Discovering future cures from phytochemistry to metabolomics - Shaari, Khozirah (Universiti Putra Malaysia Press, 2015)
Eukaryotes such as higher plants have evolved to produce a diverse range of low-molecular-weight compounds known as secondary metabolites or phytochemicals, that can be used as food and feed additives, flavours, fragrances, cosmetics, agrochemicals and pharmaceuticals. The chemical diversity of plants is more complex than any chemical library made by humans, and the plant kingdom therefore represents an enormous reservoir of valuable molecules just waiting to be discovered. There are approximately 298,000 species of higher plants, less than 10% of which have been chemically characterized to any extent. The majority of plant species are found in tropical rain forests. Extracts and infusions containing natural products from plants have historically been a major source of pharmaceutical ingredients, often comprising mixtures of several bioactive compounds with complex synergistic effects. The first secondary metabolite isolated from plants was morphine (over 200 years ago) and many other natural compounds have since become important pharmaceuticals in modern society. It is often difficult to find synthetic substitutes with the same efficacy and specificity as natural compounds. Consequently, molecules derived from plants make up a sizeable proportion of current high-value drugs, and also provide many new lead compounds for industrial applications. Many companies are undergoing a renaissance in their interest in plant-derived compounds, especially the pharmaceutical industry looking for new drugs, and the cosmetics industry which uses plant extracts, oils and even plant cell cultures in some products. The high structural diversity and complexity of secondary metabolites still pose technical challenges for a phytochemist since the chemical characteristics of the plant compounds vary to a very high degree, for example in the degree of polarity and solubility. Typically such compounds accumulate at low levels in plant tissues and production is strongly correlated to specific vegetative stages. Thus the process of finding, extracting, isolating and purifying these phytochemicals is time-consuming and can be a daunting and challenging task. Further many plants that produce high-value secondary metabolites are difficult to cultivate or are endangered because of over-harvesting and deforestation activities. However, the last decade has seen tremendous development in technology and the birth of new, innovative methods that are now accessible for use by the current generation of researchers. In some cases, what was impossible to do then has become almost routine now. Armed with these new advantages and strength, the continuous exploration of plant biodiversity, using novel and innovative bioassays to evaluate natural compounds for their beneficial effects, is therefore of great scientific, medical and bioeconomic importance. In this inaugural lecture, some highlights of my journey and discoveries made, together with my colleagues and students that I have worked with over the last 15 years of natural products research, will be presented. Our research endeavours which began with a mainly reductionist perpective, in accordance with the then popular drug discovery approaches used by big pharmas and academic laboratories all over the world, has now mellowed into a more holistic approach, utilizing ‘omics’ technologies. Sample size and loss of biological activity due to the reductionist approach of disturbing the inherent synergism of a plant metabolome, has always been a delimiting factor in phytochemistry studies. We believe that systems biology, in particular metabolomics/metabonomics, holds greater promise in our efforts to gain a deeper understanding of a plant metabolome’s effects on a disease state or on other biological perturbations.